Respuesta :
2(c-5)-2=8+c
We simplify the equation to the form, which is simple to understand
2(c-5)-2=8+c
Reorder the terms in parentheses
+(+2c-10)-2=8+c
Remove unnecessary parentheses
+2c-10-2=+8+c
We move all terms containing c to the left and all other terms to the right.
+2c-1c=+8+10+2
We simplify left and right side of the equation.
+1c=+20
We divide both sides of the equation by 1 to get c.
c=20
We simplify the equation to the form, which is simple to understand
2(c-5)-2=8+c
Reorder the terms in parentheses
+(+2c-10)-2=8+c
Remove unnecessary parentheses
+2c-10-2=+8+c
We move all terms containing c to the left and all other terms to the right.
+2c-1c=+8+10+2
We simplify left and right side of the equation.
+1c=+20
We divide both sides of the equation by 1 to get c.
c=20